The aggregate effects of government income transfers shocks: EU evidence - Susana Párraga Rodríguez (SERIEs - Journal of the Spanish Economic Association, 2023)
This paper estimates the aggregate effects of government income transfers shocks for a sample of EU countries. I construct a new measure of transfers shocks based on a dataset by public finance experts of the European System of Central Banks (ESCB). The identification strategy consists of a narrative analysis of policy actions in old age pensions reported in the ESCB dataset. I find that increases in old age pensions have a positive impact on aggregate expenditure components and employment consistent with a multiplier effect between 0 and 1.
Keywords: E2; E62; H55; I38; 330; European Union; Fiscal multiplier; Public pensions; Transfer payments